The complete mitochondrial genome of Rhacophorus dennysi (Anura: Rhacophoridae) and phylogenetic analysis. (2nd September 2016) - Huang, Minyi; Lv, Tong; Duan, Renyan; Zhang, Siyu; Li, Hairong
Abstract: Rhacophorus dennysi is one species of the family Rhacophoridae. In this study, we sequenced the complete mitochondrial genome of R. dennysi. The complete mitochondrial genome of R. dennysi was 17 572 bp in length (GenBank accession number KT191129). Similar to the typical mtDNA of amphibians, the complete mtDNA sequence of R. dennysi contained two rRNA genes, 22 tRNA genes, 13 protein-coding genes (PCGs), and one D-loop region. The complete mitogenome sequence data in R. dennysi would provide a basis and important molecular data for studying the phylogenetic relationship, molecular identification and evolutionary analysis in anura species. The results will be useful for the detailed study of mitogenome evolution and the phylogenetic relationships among the orders in the class Rhacophoridae.